Synthesis of TiO2/SnO2 Composite Nanowire Arrays via Electrophoretic Deposition Method - Li, Jianjun; Zhang, Liting (Asian Journal of Chemistry, 2012)
Highly ordered TiO2/SnO2 composite nanowire arrays were synthesized by electrophoretic deposition method using anodic aluminium oxide as template. Careful structural characterization indicates that the prepared composite nanowires are composed of small nano-crystallines of rutile TiO2 and tetragonal SnO2 with amorphous grain boundaries. The mechanism of the electrophoretic deposition is discussed.